Educational services sphere as a tool for improving the quality of human resources in the region - L. V. Agarkova; E. A. Ostapenko (Вестник университета)
The educational services sphere of Stavropol Krai occupies a significant place in the Russian economic sector development, as its main task is to meet the needs of the region, which is currently receiving special attention from the state, in qualified personnel. It is the end result of the functioning of the sphere that is a reliable foundation for human resources formation in this constituent entity. The role of education and human resources in the development of the regional economy of Stavropol Krai has been considered. The influence of the educational system on qualified specialists training necessary for sustainable development of the regional economy has been analyzed. The main trends and challenges related to education development in the region have been studied, and practical recommendations for optimizing educational programs and improving the quality of training offered. Particular attention has been paid to the issues of training highly qualified personnel and creating favorable conditions for their retention in the region. The influence of the human factor on educational services development in the region by means of SWOT-analysis has been considered. The purpose of the study is to develop institutional tools for the human factor development in the educational services sphere. The objective of the study is the identification of forms and issues of human factor development in the sphere. The research methodology is represented by institutional analysis and statistical method, SWOTanalysis is also applied. The results obtained can be used for forming and implementing a strategy for improving the education system in order to increase the region’s competitiveness.